PENGARUH MUSIK DENGAN TEMPO CEPAT & LAMBAT TERHADAP ATENSI MAHASISWA - Christ Billy Aryanto; Rhesa Megananda (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2019)
This study aims to investigate the effect of listening to music with fast and slow tempo onundergraduate student’s attention. Music is used to accompany students in carrying out activitiesin daily life. The results of previous studies have shown that music can be a distraction when theywere doing their work, but other studies have shown that music has no effect on attention. Attentionis the first stage in the cognitive process, which is the starting point for a person’s cognitiveproesses to finally create a memory. In this study, an experiment with within-subject design wascarried out by listening to music with a different tempo when doing an attention test. Fourteenundergraduate students aged 21-23 years were involved in this study by completing 3 forms ofConcentration Grid Test in 3 different conditions, namely while listening to instrumental popmusic with fast tempo, slow tempo, and in a silence. The results of repeated measures ANOVAshowed that there was an effect of tempo on students’ attention with F(2.26) = 6.84, p<0.05. Theresults of the contrast analysis showed that participants who listened to instrumental pop musicwith a slow tempo had a significantly higher score that fast tempo (t = 3.433, p<0.01) and control(t = 2.908, p<0.01), but fast tempo instrumental pop music has no significant difference withcontrol (t = 0.525, p = 0.604). Thus, slow tempo music can increase the attention, but instrumentalpop music with fast tempo does not distract the students.